Why are the axioms for vector space independent?

More precisely $1x=x$ seems redundant...

(I take the axioms from: Wikipedia)


One has for zero vector: $$\lambda0+\lambda0=\lambda(0+0)=\lambda0\implies\lambda0=0$$

And for zero scalar: $$0x+0x=(0+0)x=0x\implies0x=0$$

In familiar form: $$\lambda x=0\implies\lambda=0\lor x=0$$

Threrefore one calculates: $$1(1x+x^{-1})=1(1x)+1(x^{-1})=(11)x+1(x^{-1})=1x+1(x^{-1})=1(x+x^{-1})=10=0$$

Hence for nontrivial field: $$1\neq0\implies1x+x^{-1}=0\implies1x=x$$

But where is the flaw in that check??

  • 1
    $\begingroup$ I'm guessing you're using these axioms? $\endgroup$ May 15, 2015 at 20:42
  • 4
    $\begingroup$ What is $x^{-1}$? In a vector space we do not necessarily have multiplicative inverses. Do you mean $-x$? $\endgroup$ May 15, 2015 at 20:44
  • 9
    $\begingroup$ @GregoryGrant $x^{-1}$ is (bad) notation for $-x$. $\endgroup$ May 15, 2015 at 20:45
  • 1
    $\begingroup$ @CameronWilliams Ah got it, yes that is bad. $\endgroup$ May 15, 2015 at 20:45
  • 2
    $\begingroup$ We're actually using $1a=a$ to deduce $0a=0$. @Freeze_S $\endgroup$ May 15, 2015 at 20:46

4 Answers 4


The axiom system you quote does not have $$\lambda x=0\implies \lambda=0 \lor x=0 $$ as an axiom.

If we drop the axiom $1v=v$, the following becomes an example of a "vector space" over $\mathbb R$:

  • $V=(\mathbb R,+)$, $F=(\mathbb R,+,\cdot)$
  • for $\lambda \in F$ and $v\in V$ let $\lambda v=0$.

We do not want this to happen.

  • $\begingroup$ I think you may have nailed it. $\endgroup$ May 15, 2015 at 20:53
  • $\begingroup$ But I didn't assume this, I prove it! $\endgroup$ May 15, 2015 at 20:53
  • 4
    $\begingroup$ @GregoryGrant Sometimes a simpe counterexample is simpler than a seventeen comment discussion :) $\endgroup$ May 15, 2015 at 20:55
  • 1
    $\begingroup$ @Freeze_S Simple. To conclude from $\lambda0=0$ and $0x=0$ that $\lambda x=0\implies \lambda=0\lor x=0$ is a non-sequitur. For example in the ring $\mathbb Z/4\mathbb Z$ we have $\lambda 0=0$ and $0x=0$ for all $\lambda, x$, but $\lambda x=0\not\implies \lambda=0\lor x=0$ because $\lambda=x=2+4\mathbb Z$ is a counterexample. $\endgroup$ May 15, 2015 at 20:56
  • 2
    $\begingroup$ @Freeze_S You did not prove $\lambda x=0\implies \lambda=0$ or $x=0$. You proved the other implication. $\endgroup$ May 15, 2015 at 20:57

A mistake: You only showed that $\lambda=0$ or $x=0$ $\implies$ $\lambda x=0$. You did not show the reverse implication: $\lambda x=0 \implies \lambda=0$ or $x=0$. A proof of that implication uses the axiom $1x=x$.

A standard counterexample of a structure that satisfies all the other axioms save $1x=x$ is the following:

  • $V=\Bbb{F}^2$
  • $(x_1,x_2)+(y_1,y_2)=(x_1+y_1,x_2+y_2)$, i.e. the usual componentwise vector addition
  • $a*(x_1,x_2)=(ax_1,0)$.

The system $(V,+,*)$ satisfies all the other axioms but $1x=x$. Note that that reverse implication does not hold in this system: $$1*(0,1)=(0,0)=0_V.$$


In order to prove $$ \lambda x=0\implies \lambda=0\vee x=0\tag1 $$ you need to use the axiom $1x=x$.

Here is how you prove (1): if $\lambda\neq0$, then $\lambda x=0$ implies $$ \lambda^{-1}(\lambda x)=\lambda^{-1}(0) $$

$$ (\lambda^{-1}\lambda)x= 0 $$ $$ 1x =0 $$ $$x=0$$ so $\lambda\neq0$ implies $x=0$, or equivalently, $\lambda=0\vee x=0$.

Thus, your proof of the axiom $1x=x$ being redundant goes in circles.


The axioms of the list you cite are not independent, but $1x=x$ is not the problem.

Commutativity of addition follows from the other axioms; let $x,y\in V$ and set $$ z=(1+1)(x+y) $$ Then $$ z=1(x+y)+1(x+y)=x+y+x+y $$ (parentheses can be omitted because of associativity). On the other hand $$ z=(1+1)x+(1+1)y=1x+1x+1y+1y=x+x+y+y $$ Therefore, being $V,+$ a group, we can do $$ (-x)+x+y+x+y+(-y)=(-x)+x+x+y+y+(-y) $$ which gives $$ y+x=x+y $$

An correct objection would be that, removing the commutativity of addition axiom, only right zero and right opposites are assumed. However a general result about monoids applies.

Let $M$ be a (multiplicative) semigroup, with right identity $e$. If every element has a right $e$-inverse, then every element has a left $e$-inverse and the right identity $e$ is also a left identity.

The assumption is that $ae=a$, for all $a\in M$, and that, for all $a\in M$, there exists $b\in M$ such that $ab=e$.

Let $a\in M$ and $b\in M$ such that $ab=e$. Then $bab=be=b$, so, if $c\in M$ and $bc=e$, we have $babc=bc$, hence $ba=e$. Moreover, $ea=aba=a$. Thus $e$ is also a left identity and $b$ a left inverse of $a$.

  • $\begingroup$ The commutativity axiom is indeed redundant, but your proof is incomplete. The list only postulates the existence of right zero and right inverses, not left zero or left inverses, so you need to prove those. $\endgroup$ May 16, 2015 at 15:21
  • $\begingroup$ @EmilJeřábek Done. $\endgroup$
    – egreg
    May 16, 2015 at 15:38

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .